Policing cryptocurrencies - Zulhuda, Sonny (New Straits Times Press (M) Berhad, 2017)
Cryptocurrency is a digital currency in which encryption techniques are used to regulate the generation of units of currency and verify the transfer of funds, operating independently of the banking system. It is an emerging financial technology enabled by innovation and is increasingly popular among Internet users. It challenges financial and regulatory rules on currency and payment systems. In Malaysia, Bank Negara Malaysia (BNM) was recently quoted in the New Straits Times as saying that guidelines governing cryptocurrencies were expected to be unveiled by the end of the year. This announcement is timely.